Pulsed current activated synthesis and consolidation of a nanostructured Cr2Zr-ZrO2 composite and its mechanical properties - Shon, In-Jin; Yoon, Jin-Kook; Hong, Kyung-Tae (세라믹공정연구센터, 2017)
ZrO2 has been used for hip and knee joint replacements because of the excellent combination of biocompatibility, low density and corrosion resistance. However, coarse-grained ZrO2 has low wear, abrasion resistance and fracture toughness. One of the methods to improve mechanical properties is generally to refine the grain size. As nanomaterials possess high strength, high hardness, excellent ductility and toughness, undoubtedly, more attention has been paid for the application of nanomaterials Cr2Zr-1.5ZrO(2) composite was simultaneously synthesized and consolidated by pulsed current activated heating within two min from mechanically milled powders. Highly dense nanostructured Cr2Zr-1.5ZrO(2) composite with a relative density of up to 98.5% was produced under application of an 80 MPa pressure with the pulsed current. The mechanical properties and microstructure of the Cr2Zr-1.5ZrO(2) composite was investigated using Vickers hardness measurement, X-ray diffraction analysis and Scanning electron microscope observation.